The patterns of negotiation of meaning in synchronous computer-mediated classroom discussions - Abdul Ghani, Rozina (IIUM Press, 2017)
This book discusses the patterns of negotiation of meaning in an open-ended small group synchronous computer-mediated classroom discussion (CMCD) amongst intermediate ESL/EFL learners. Most research has dwelled on the quantitative aspect of online discussion between dyads. There is, however, a dearth of research on the quality of non-native speakers’ online interaction conducted in small groups. In this study, a purposeful sampling of 67 students from three intermediate ESL/EFL classes engaged in synchronous online classroom discussion. The data were gathered from the discourse analysis of the online discussion, the content analysis of the participant observation, semi-structured interview of all the students and the course documentation. The data of the students’ discussion triangulated with the descriptive statistics of their online output, the semi-structured interviews, the participant observation and course documentation demonstrated that well-defined open-ended tasks could indeed foster negotiation of meaning. The rigorous analysis reveals quality negotiation of meaning even though the quantity was relatively small. The learners, however, seldom modified their interlanguage towards the target language form. Lexical and content difficulties triggered most of the negotiations. The negotiation experience also led the learners towards metalinguistic awareness through self-correction and corrective feedback within and outside the negotiation routines. In addition, the students liked the textual nature of online communication. Students perceived that open-ended tasks were meaningful as they were compelled to use a wide range of vocabulary and structures. This study demonstrates that language task, classroom management, learners' language proficiency and computer skills are important factors to be considered when incorporating CMCD into teaching and learning as these may affect the linguistic quality of online negotiation.